The use of aromatherapy in primary dysmenorrhea - Ristiani; Aryadi Arsyad; Andi Nilawati Usman; Saidah Syamsuddin; Mardiana Ahmad; Andi Wardihan Sinrang (Elsevier, 2021)
Objective: The purpose of this review is to determine the use of aromatherapy in primary dysmenorrhea. Method: This is a literature review by searching article databases through Google Scholar, PubMed, ScienceDirect, Microsoft Academic, ProQuest, Semantic Scholar. The selection period for article publication is from 2015 to 2021. A total of 96 articles were obtained, and 30 articles could be entered according to the inclusion criteria. Results: Thirty articles were analyzed, it is shown that aromatherapy effectively reduces the intensity of primary dysmenorrheal pain. The sample size of the 30 articles varied from 16 samples to 200 research samples, and the research design used experiments, clinical trials, and ex vivo, in vivo, and in vitro studies. Conclusion: Aromatherapy is an effective alternative intervention that can be used to reduce the intensity of primary dysmenorrhea pain.